2023
DOI: 10.3389/fnhum.2022.1029554
|View full text |Cite
|
Sign up to set email alerts
|

Orexin dual receptor antagonists, zolpidem, zopiclone, eszopiclone, and cognitive research: A comprehensive dose-response meta-analysis

Abstract: BackgroundAbout one-third of adults have trouble sleeping, ranging from occasional difficulty to chronic insomnia, along with difficulty maintaining sleep. Many studies reported that the long-term use of hypnotics can cause brain dysfunction and damage cognition.ObjectiveThe objective of the study is to evaluate whether low, medium, and high doses of orexin dual receptor antagonists (DORA), zopiclone (ZOP), eszopiclone (ESZ), and zolpidem (ZST) can impair cognition.MethodsFrom the beginning through September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In addition to improving sleep-wake homeostasis, therapeutics aimed at preserving ORX systems could also lead to deterring AD progression. Various studies on rodents and in vitro models have demonstrated that ORX administration and/or ORX receptor modulation induce neuroprotection and restore sleep-wake homeostasis by modulation of AKT phosphorylation, ERK pathways, and inflammation [31][32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to improving sleep-wake homeostasis, therapeutics aimed at preserving ORX systems could also lead to deterring AD progression. Various studies on rodents and in vitro models have demonstrated that ORX administration and/or ORX receptor modulation induce neuroprotection and restore sleep-wake homeostasis by modulation of AKT phosphorylation, ERK pathways, and inflammation [31][32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Allosteric activation of ATPV0D1, a key component of v-ATPase, is critical for lysosomal acidification. ATP6V0D1 knockdown leads to a significant decline in cell survival and loss of lysosomal acidity in PC12 cells and induces neurodegeneration in rodent models of diabetic neuropathy 61 . In addition, inhibition of ATP6V0D1 can inhibit macrophage autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…These agents have shown similar early efficacy and potentially superior cognitive safety to Z-Drugs, a relevant consideration in the treatment of older adults. 162 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the treatment of insomnia is essential in patients with chronic pain especially using dual orexin receptor antagonists that have demonstrated high efficacy in inducing and maintaining sleep without impairing cognition (Adamo et al, 2021 ; Zhou et al, 2023 ).…”
mentioning
confidence: 99%